2003
DOI: 10.1007/s00440-003-0309-8
|View full text |Cite
|
Sign up to set email alerts
|

Time-fractional telegraph equations and telegraph processes with brownian time

Abstract: We study the fundamental solutions to time-fractional telegraph equations of order 2α. We are able to obtain the Fourier transform of the solutions for any α and to give a representation of their inverse, in terms of stable densities. For the special case α = 1/2, we can show that the fundamental solution is the distribution of a telegraph process with Brownian time. In a special case, this becomes the density of the iterated Brownian motion, which is therefore the fundamental solution to a fractional diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(61 citation statements)
references
References 12 publications
4
52
0
5
Order By: Relevance
“…and recalling that L −1 {s −δ } = t δ−1 / (δ) (δ > 0) [57], we get the exact expression for the mean square displacement [48] …”
Section: Time-fractional Telegrapher's Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…and recalling that L −1 {s −δ } = t δ−1 / (δ) (δ > 0) [57], we get the exact expression for the mean square displacement [48] …”
Section: Time-fractional Telegrapher's Equationmentioning
confidence: 99%
“…During the last decade a number of works have appeared in the mathematics literature, particularly those of Orshinger and collaborators [47][48][49], analyzing mathematical and other formal properties of the FTE. However, the fractional equation is set in an ad hoc fashion by replacing the ordinary derivatives that appear in the TE by fractional derivatives which, in addition, may be of various types [49].…”
Section: Introduction and General Scopementioning
confidence: 99%
“…However, for the sake of simplicity and briefness, we have not treated them here, and we will deal with these questions in a future work. In any case, we address the interested reader to the works of Mainardi and collaborators [46,47,62,64] on solutions for fractional diffusion and fractional wave-diffusion equations and to Orsingher and collaborators [65][66][67] on several kinds of solutions to the FTE.…”
Section: Discussionmentioning
confidence: 99%
“…[50,66] for further details). From this exact expression it easily is shown that the mean square displacement exists and that is approximated by…”
Section: Discussionmentioning
confidence: 99%
“…What we will discuss is the following time-fractional telegraph equation [13]: As for the boundary condition, we consider the Dirichlet boundary condition, …”
Section: Introductionmentioning
confidence: 99%